DIFFERENCES IN THE NUTRITIONAL STATUS OF YOUNG SCHOOL CHILDREN FROM PUBLIC AND PRIVATE OWNED PRIMARY SCHOOLS IN EKITI STATE, NIGERIA - J. A. Adegun; O. B. Ajayi-Vincent; E. O. Alebiosu (European Scientific Journal, ESJ, 2013)
This paper investigated the nutritional status of a randomly selected school age children from public and private owned primary schools in Ekiti State, Nigeria with the aim of determining if differences exist between them and providing a baseline data for the state in this regard. Four hundred and fifteen (415) children with their age range between 4 and 10 years participated in the study. Anthropometric measurements were carried out and Body mass index (BMI) was used as a measure of physical growth. Percentage and frequency counts, mean (X) and standard deviation (sd) were used to describe the data while student “t” test set at 0.05 was used to test the significant difference between means from the two groups of school children. The findings revealed that the nutritional status of the school children was generally poor and a significant difference existed between the school children from the public and private owned primary schools in Ekiti State with the School Children from Private owned Primary schools having a higher nutritional status than the school children from public primary schools. Improved nutrition enlightenment and feeding approaches were recommended for the parents and the government.